THE ROLE OF GAMIFICATION IN ENHANCING CRITICAL THINKING SKILLS IN ONLINE SCIENCE EDUCATION - AHMED, Adedolapo Abdulahi; OYEYIPO, Ademola Olakunle; YUNUS, Sulyman Ayinla; UMAR, Madiwu Abubakar (Fakultas Pertanian, 2025)
This study examines the role of gamification in enhancing critical thinking skills in online science education, centring on the impact of specific game-based elements and learner cognitive behaviour. The research question examines which gamification features best enhance critical thinking and how motivation and prior knowledge influence possible outcomes. Using a quantitative research design with a survey method, a sample of 600 students was selected from three universities with 200 participants from each institution by a multi-stage sampling technique, initially identifying the science education departments and then selecting participants through simple random sampling of the 400-level students. A researcher-design instrument was used to collect data. Data were analysed using descriptive and inferential statistics, including regression analysis, to assess the relationship between gamification elements and critical thinking skills. Results revealed that gamification, particularly reflection tasks and progress-tracking, significantly aids critical thinking by promoting self-assessment and engagement. However, competitive elements like leaderboards proved less effective, indicating a need for balance in gamified educational learning designs. The study recommends structured reflection tasks and progress tracking for online learning. This suggests gamification's potential to enhance critical thinking when directed to varied learner profiles.